The Wife’s Role of the Pastor of Indonesian Baptist Church BPD Jatengbagut Mranggen Area To Help Husbands in Pastoral Service: Peran Istri Gembala Sidang Gereja Baptis Indonesia BPD Jatengbagut Rayon Mranggen Untuk Menolong Suami Dalam Pelayanan Pastoral - Elisa Br Sihite; Eko Wahyu Suryaningsih; Ayin Claudia (Sekolah Tinggi Teologi Baptis Indonesia, 2022)
The call to become a pastor's wife is a noble call for those who are ready to serve God. God created the wife as a worthy helper for the husband, and helped the husband in the ministry. Thus a shepherd's wife must truly believe in God and love God. The faithfulness and perseverance of a pastor's wife in a life based on the Christian faith will be a blessing and a good asset for her husband's pastoral ministry. However, the problem faced in pastoral care, especially in the Mranggen area, is the existence of obstacles for the wives of pastors related to their duties and responsibilities outside the pastoral service itself. The purpose of this study was to determine the role of the wives of the pastors of the Indonesian Baptist Church BPD JATEGBAGUT Rayon Mranggen to help their husbands in pastoral care. Through a qualitative approach using interviews with 6 wives of the pastor of the Indonesian Baptist Church BPD JATEGBAGUT Rayon Mranggen as participants, this study concludes that pastoral care is a service carried out by the pastor to help, guide, teach or direct the congregation being served. The pastor's wife must understand the pastoral ministry that her husband does as a pastor, which is to know every condition of the congregation being served and to help the congregation to grow in faith in God. The pastor's wife must be able to carry out her role in the congregation, in the family, and in society well and be responsible for helping her husband's pastoral ministry.